(3hUa Ojf GdEeGejIs - (3Gdbej, , GHf HGHhjg, GdTjN GdUOhb, GHf HGHhjg Gdbej, eMeO Hf Ydj Hf GdMSjf, GdeYQha HGdTjN GdUOhbs ((3cGTa GdZWGAs)
(3ChdgG (B:s
(3ChdgG(B: (3Ojf GdEeGejI gh GdEbQGQ HJhMjO Gddg JYGdi PcQg hfaj GdJTHjg Yfg hJfRjgg YeG dG jdjb Hg hGdEbQGQ HCf eMekOG gh SjO GdCfHjGA hGdeQSdjfs
(3BNQgG (B:s
(3BNQgG(B: (3hSCedj TQM Pdc hJaSjQg EPG Sgd Gddg YR GSeg Ydj GdYhO ef ebUOj Edi fjSGHhQ (B.. (3Je hceds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI, L (B2: 128s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdJhMjO hGdedd hGdfMds